Methods for the valorisation of agri-food waste according to the circular bioeconomy concept - Kaim, Urszula (Kierunki zagospodarowania odpadów rolno-spożywczych w biogospodarce o obiegu zamkniętym, 2021)
Waste management represents a global and ever-growing issue attracting more attention according to environmental, ethical, social and economic implications. Some of the most significant waste produced globally is generated in the agri-food sector (AFS). AF residues often represent a resource of valuable substances that should be recycled and reused. Making full use of the potential in AF waste (AFW) is in line with the concept of a circular bioeconomy. This approach is consistent with the strategic elements of sustainable development, according to which the economy and society are being reorganised. The full utilisation of secondary raw materials associated with transforming primary waste into raw materials for further production increases income for entrepreneurs and reduces risks to the environment. This paper presents the concepts and legal basis of the closed-loop bioeconomy in the European Union and the metathesis of waste management from the AFS according to this model.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2021, Nr 37, s. 94-112
Keywords: circular bioeconomy; sustainable developmeny; agri-food waste; waste management hierarhy; SCP; biodegradable composites; biogospodarka cyrkularna; zrównoważony rozwój; odpady rolno-spożywcze; hierarchia postępowania z odpadami; białko jednokomórkowców; kompozyty biodegradowalne